The potential impact of allied health professional telehealth consultations on health inequities and the burden of treatment - Nicola Eddison; Enza Leone; Aoife Healy; Carolyn Royse; Nachiappan Chockalingam (BMC, 2022)
Abstract Background The COVID-19 pandemic resulted in a rapid shift to remote consultations. The study aimed to explore the prevalence of telehealth consultations amongst allied health professional (AHP) services in the UK National Health Service (NHS), and the potential impact on health inequities and burden of treatment for patients. Methods Cross-sectional online survey. Participants were practising UK registered AHP and/or AHP service manager in an NHS/social care/local authority service. Data was collected between May - June 2021. Results 658 participants took part in this study, including 119 AHP service managers, managing a total of 168 AHP services, and 539 clinicians. 87.4% of clinicians and 89.4% of services represented were using telehealth consultations as a method of delivering healthcare, the majority reported their services were planning to continue using telehealth post COVID-19 restrictions. Participants reported a lack of technological skills for patients as the most prevalent barrier affecting the patient's ability to conduct a telehealth consultation, followed by a lack of technology for patients. These were also reported as the biggest disadvantages of telehealth for patients. The majority of clinicians reported a reduction in the cost of parking/transport to attend hospital appointments as a patient benefit of telehealth consultations. Reported benefits for clinicians included saving travel time/costs and allowing flexible working, while benefits to the AHP service included patient flexibility in how their appointments are conducted and reducing the potential exposure of staff to communicable diseases. Conclusions The current large-scale implementation of telehealth in NHS AHP services may increase disparities in health care access for vulnerable populations with limited digital literacy or access. Consequently, there is a danger that telehealth will be considered inappropriate and thus, underutilised, negating the potential benefits of sustainability, patient empowerment and the reduction in the burden of treatment.